The Rate of Return to Early Childhood Education in Japan: Estimates from the Nationwide Expansion - Hideo Akabayashi; Ryuichi Tanaka (Institute of Labor Economics (IZA), 2024)
We present new estimates of the internal rate of return to early childhood education. Utilizing the nationwide expansion of preschool education in Japan between 1960 and 1980, we initially assess the impact of preschool attendance on high school graduation and college enrollment for men. Subsequently, we compute the social rate of return to preschool attendance for men by drawing upon national wage statistics to project expected wage trajectories and referencing government documents to account for the social cost of preschools. Our findings indicate a social rate of return ranging from 5.7% to 8.1%, consistent with previous estimates in the literature.
Keywords: I22; I28; H75; 330; internal rate of return; universal preschool expansion; kindergarten; nursery school